FRI0407 The Impact of Lupus Nephritis at Inception on Health Related Quality of Life: Results from an International Cohort Study. (10th June 2014) - Hanly, J.G.; O'Keeffe, A.G.; Urowitz, M.B.
Abstract : Background: Health Related Quality of Life (HRQoL) is important in systemic lupus erythematosus (SLE) for both global and organ specific disease. Objectives: To examine the association between lupus nephritis at inception and patient self-report HRQoL in a large, multi-ethnic/racial, cohort of SLE patients. Methods: An observational cohort study of new onset SLE (ACR classification criteria <15 months) was performed by an international network of 32 academic centers. Patients were evaluated at enrollment and annually. Lupus nephritis was identified as "renal disorder" in the ACR classification criteria. Using estimated glomerular filtration rate (eGFR), three GFR states were defined: state 1 (eGFR: >60 ml/min); state 2 (eGFR: 30 – 60 mL/min); and state 3 (eGFR: <30 ml/min). Similarly, using estimated urine protein excretion (ePrU), three PrU states were defined: state 1 (ePrU: <0.25 gr/day); state 2 (ePrU: 0.25 – 3.0 gr/day); and state 3 (ePrU: >3.0 gr/day). HRQoL was determined by patient self-report SF-36 subscale scores, mental (MCS) and physical (PCS) component summary scores. Statistical analyses were based on analysis of variance or equivalent t-tests. Results: There were 1, 827 patients, 89% females, predominantly Caucasian (49.2%) with a mean ± SD age of 35.1±13.3 years. The mean ± SD disease duration was 0.5±0.3 years and the mean duration of follow-up was 4.6±3.4 years. The cumulative occurrence of lupus nephritis was 38.4% and the majority of patients (71.2%) were diagnosed at enrollment. SF-36 subscale and summary scores were not significantly lower in patients with lupus nephritis compared to those without nephritis at enrollment. However, for patients with lupus nephritis at enrollment or follow-up, those in state 3 GFR had clinically and statistically significant lower scores in three subscales (Physical function, Physical role and Bodily pain) and in the Physical component summary score of the SF-36 (p<0.01) (Table 1 ). The only association between SF-36 scores and PrU states at diagnosis of nephritis was in the Role Physical subscale (Table 1 ). Conclusions: The presence of lupus nephritis in a large multi-ethnic cohort was not associated with a reduction in HRQoL. However, severe impairment in renal function and to a lesser extent heavy proteinuria, were associated with lower subscale and physical component summary scores of the SF-36. Patient self-report HRQoL is reduced in severe lupus nephritis and may be an important outcome variable in clinical trials of renal disease in SLE. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1114